Development of a Monopoly-Based Educational Game to Enhance Elementary Students’ Understanding of Indonesia’s Geographical Location - Pratiwi, Desiana Retno Rizki; Fathurrahman, Moh. (Jurnal Pendidikan Progresif, 2025)
Development of a Monopoly-Based Educational Game to Enhance Elementary Students’ Understanding of Indonesia’s Geographical Location. Objective: The limited use of learning media by teachers in the classroom learning process affects students' learning outcomes. To enhance these outcomes, appropriate learning media are needed, especially those that align with the characteristics of elementary school students who tend to enjoy play-based activities. One such example is the Monopoly game media, which incorporates captivating images to engage students. This study aims to develop, test the feasibility, and effectiveness of the ekasi monopoly game media to improve student learning outcomes in social and natural science learning outcomes. Methods: This type of research is developmental research (R&D) using the ADDIE development model. The study involved 29 fifth-grade students at SDN Tambakaji 05 Semarang. Data collection techniques included both pretest-posttest and non-test methods, such as observations, interviews, questionnaires, and documentation. Findings: The results indicated that the feasibility of the Ekasi Monopoly Game Media was assessed by media experts at 93.3%, material experts at 97.5%, teachers at 95%, and students at 91.6%, all falling within the "very feasible" category. Additionally, based on the N-Gain test, the Ekasi Monopoly Game Media was proven to be effective, with a high effectiveness category and an average score of 0.7150. Additionally, the t-test results showed a score of 0.000 with sig < 0.05 between the pretest and posttest findings. Conclusion: To enhance the learning outcomes of the IPAS material on the geographical location of Indonesia for fifth-grade students at SDN Tambakaji 05 Semarang, the study's findings indicate that the development of the Ekasi Monopoly Game Media was completed and categorized as both highly feasible and effective. Through the development of this media, students were able to easily understand the material and remained enthusiastic about learning, as they experienced an engaging and enjoyable learning process. Keywords: learning media development; monopoly game; learning outcomes: geographical location of indonesia.